2008
DOI: 10.1111/j.1601-5223.1990.tb00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Standard karyotype of the domestic horse (Equus caballus)

Abstract: The following decisions concerning the banded karyotype of the horse (Equus caballus) were made at the second International conference for Standardization of Domestic Animal Karyotypes, held at Jouy-en Josas, France, 22nd-26th May 1989: (1) numbering of the chromosomes was modified to correspond to an arrangement into only two groups (the non-acrocentrics and the acrocentrics) within which the autosomes are placed according to length alone; (2) a more compact karyotype arrangement was adopted: chromosomes 1 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 6 publications
0
17
0
1
Order By: Relevance
“…The 32nd pair are sex chromosomes. Chromosome X is one of the largest chromosomes in the karyotype, while chromosome Y is one of the smallest (Richer et al 1990, Bowling et al 1997, Wade et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…The 32nd pair are sex chromosomes. Chromosome X is one of the largest chromosomes in the karyotype, while chromosome Y is one of the smallest (Richer et al 1990, Bowling et al 1997, Wade et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Richer et al, (1990). However, chromosomal biometry results in this work diverged from the division of karyotype into acrocentric and non-acrocentric groups, as suggested by Richer et al, (1990), since this kind of morphology is not present in the karyotype.…”
Section: Cytogenetic Characteristicsmentioning
confidence: 81%
“…Richer et al, (1990). However, chromosomal biometry results in this work diverged from the division of karyotype into acrocentric and non-acrocentric groups, as suggested by Richer et al, (1990), since this kind of morphology is not present in the karyotype. In our bibliographical survey, we observed that publications relating to the chromosomal characterization of E. caballus did not present a morphological description of each chromosome pair.…”
Section: Cytogenetic Characteristicsmentioning
confidence: 81%
See 2 more Smart Citations